2017
DOI: 10.1021/acs.jmedchem.7b00032
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of 2-[[2-Ethyl-6-[4-[2-(3-hydroxyazetidin-1-yl)-2-oxoethyl]piperazin-1-yl]-8-methylimidazo[1,2-a]pyridin-3-yl]methylamino]-4-(4-fluorophenyl)thiazole-5-carbonitrile (GLPG1690), a First-in-Class Autotaxin Inhibitor Undergoing Clinical Evaluation for the Treatment of Idiopathic Pulmonary Fibrosis

Abstract: Autotaxin is a circulating enzyme with a major role in the production of lysophosphatic acid (LPA) species in blood. A role for the autotaxin/LPA axis has been suggested in many disease areas including pulmonary fibrosis. Structural modifications of the known autotaxin inhibitor lead compound 1, to attenuate hERG inhibition, remove CYP3A4 time-dependent inhibition, and improve pharmacokinetic properties, led to the identification of clinical candidate GLPG1690 (11). Compound 11 was able to cause a sustained re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
130
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 120 publications
(131 citation statements)
references
References 42 publications
1
130
0
Order By: Relevance
“…Reduction in LPA C18:2 was also apparent in the pooled placebo group, only in the MAD part of the study; however, this was highly variable, and there was clear separation between placebo and GLPG1690 (even at the lowest dosage) in effects on LPA C18:2. These results indicate that GLPG1690 inhibited autotaxin effectively . After 14 days of GLPG1690 administration, plasma LPA C18:2 was reduced at predose by at least 70% for all doses; for GLPG1690 600 mg once daily and 1000 mg once daily, this finding indicates that GLPG1690 concentration remained at a level capable of inhibiting autotaxin for at least 24 hours postdose and that once‐daily dosing is sufficient.…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…Reduction in LPA C18:2 was also apparent in the pooled placebo group, only in the MAD part of the study; however, this was highly variable, and there was clear separation between placebo and GLPG1690 (even at the lowest dosage) in effects on LPA C18:2. These results indicate that GLPG1690 inhibited autotaxin effectively . After 14 days of GLPG1690 administration, plasma LPA C18:2 was reduced at predose by at least 70% for all doses; for GLPG1690 600 mg once daily and 1000 mg once daily, this finding indicates that GLPG1690 concentration remained at a level capable of inhibiting autotaxin for at least 24 hours postdose and that once‐daily dosing is sufficient.…”
Section: Discussionmentioning
confidence: 75%
“…GLPG1690 is a first‐in‐class autotaxin inhibitor currently being investigated as a novel therapy for IPF . This first‐in‐human study demonstrated that GLPG1690 was well tolerated after administration of single doses up to 1500 mg and multiple doses up to 1000 mg once daily for 14 days.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations